Penyuluhan Hukum Mencegah Tindak Pidana dalam Pembagian Warisan pada Masyarakat Desa Kutomulyo Biru-Biru - Maswandi Maswandi; Riswan Munthe; Fauzi Wikanda (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to educate and raise awareness of inheritance law and criminal law, both national and Islamic, through seminars, community group discussions, and direct community outreach. This legal outreach activity aims to increase legal awareness and understanding in the community of Kutomulyo Village, Biru-Biru District. Mentoring and Workshops: Assisting the community in recognizing, reporting, and handling cases of inheritance embezzlement, as well as training in calculating inheritance rights under civil and Islamic law. Collaboration between Village Officials, Religious Leaders, and the Village Community: Involving religious leaders and village officials to strengthen legal understanding. Evaluation and Reflection: Conducting regular evaluations of community understanding and behavioral changes. Through this legal outreach, it is hoped that the community will be able to resolve inheritance issues fairly, in accordance with legal provisions, thereby minimizing the potential for criminal acts in inheritance distribution.